FRI0507 COLCHICINE INTOLERANCE IN FMF PATIENTS AND PRIMARY OBSTACLES FOR OPTIMAL DOSING. (2nd June 2020) - Satiş, H.; Armagan, B.; Bodakci, E.; Atas, N.; Sari, A.; Yapar, D.; Yasar Bilge, N. S.; Bilici Salman, R.; Yardimci, G. K.; Babaoglu, H.; Kiliç, L.; Ozturk, M. A.; et al.
Abstract : Background: Colchicine is the mainstay of treatment in FMF. However, in daily practice it is not easy to maintain effective colchicine doses in substantial number of patients, due to its side effects. Objectives: It was aimed to investigate prevalence and risk factors for colchicine side effects that limit optimal drug dosing and permanent discontinuation. Methods: All patients were recruited from "FMF in Central Anatolia" (FiCA) cohort, 915 adult subjects with minimum follow up time of 6 months and had compliance of treatment were included. Demographic and anthropometric data, FMF disease characteristics, disease severity, complications and treatment features were recorded on a web based registry. Prevalence of colchicine intolerance and characteristics of intolerant patients were analyzed. Results: Effective colchicine doses cannot be maintained in 172 (18.7%) subjects. Main side effects that limit optimal dosing were as follows; diarrhea in 99 (10.8%), elevation in transaminases in 54 (5.9%), leukopenia in 10 (%1.1), renal impairment in 14 (1.3%), myopathy in 5 (0.5%) and allergic skin reaction in two. Colchicine had to be permanently ceased in 18 (2%) patients because of serious toxicity. Male gender and obesity were found to be associated with liver toxicity and having normal body weight was associated with diarrhea. Chronic inflammation and proteinuria were more common in colchicine intolerant patients and they had reported more frequent attacks compared to those tolerating optimal doses. Conclusion: Colchicine intolerance is an important problem in daily clinical practice, mainly due to diarrhea and liver toxicity. Suboptimal colchicine dosing associated with complications. References: [1] Sönmez, H.E., E.D. Batu, and S. Özen, Familial Mediterranean fever: current perspectives. Journal of inflammation research, 2016. 9 : p. 13. [2] Sari, İ., M. Birlik, and T. Kasifoğlu, Familial Mediterranean fever: an updated review. European journal of rheumatology, 2014. 1 (1): p. 21. [3] Ozen, S., et al., EULAR recommendations for the management of familial Mediterranean fever. Annals of the rheumatic diseases, 2016. 75 (4): p. 644-651. Disclosure of Interests: Hasan Satiş: None declared, Berkan Armagan: None declared, Erdal Bodakci: None declared, Nuh Atas: None declared, Alper Sari: None declared, Dilek Yapar: None declared, Nazife Sule Yasar Bilge: None declared, reyhan bilici salman: None declared, Gözde Kübra Yardimci: None declared, Hakan Babaoglu: None declared, Levent Kiliç: None declared, mehmet akif ozturk: None declared, Berna Goker: None declared, seminur haznedaroglu: None declared, Umut Kalyoncu Consultant of: Abbvie, Amgen, Janssen, Lilly, Novartis, UCB, Timuçin Kaşifoğlu: None declared, abdurrahman tufan: None declared